Sample estimation of distribution parameters if upper and lower bounds of random variable are known - Barannik, V.O. (Вопросы атомной науки и техники, 2015)
The point and interval distribution parameter estimators are obtained by direct numerical approximation of the definition integral with the use of upper and lower bounds of distributed random variable. Like in Bayesian estimation, the distribution parameters are treated as random variables, and their uncertainty is described as a distribution. The Monte Carlo procedure is involved to get the posteriori parameter distributions and the correspondent confidence interval limits.